The expression and significance of indoleamine -2,3 -dioxygenase in non-small cell lung cancer cell - Zhengtang CHEN; Jianteng GU; Yali WANG; Bo ZHU; Qichao XIE; Lingli WANG (Chinese Journal of Lung Cancer, 2008)
Background and Objective Immune tolerance plays the key role in the initiation,development and metastasis of the malignant disease.However,the underlging mechanisms have not been completely elucidated. The aim of this study is to investigate the expression of indoleamine-2,3-dioxygenase(IDO) in non-small cell lung cancer(NSCLC) and the distribution of regulatory T cell(Treg) in NSCLC tissue and the metastastic lymph node,and the possible relationships between them. Methods This study involved 62 NSCLC patients and 15 control patients with benign diseases that operated in the affiliated Xinqiao hospital and Southwest hospital of the Third Military Medical University. The expression of IDO in lung cancer cell, the corresponding normal lung tissues and the benign control tissues were detected by SP immunohistochemistry(IHC) and Fluorescent semi-quantitative RT-PCR.The distribution of Treg cell was detected by SP IHC too. The difference of positive rates of IDO was evaluated by Chi-square test and Fisher爷s exact test. Results The positive expression rates of IDO in lung cancer cells corresponding normal lung tissues and bengin disease tissues were 67.7% (42/62), 0 and 13.3% (2/15), respectively.There were significant differences between the former and the latter two (P <0.01). The positive expression rate of IDO in metastastic lymph node was 75.0%(15/20).The results of Fluorescent semi-quantitative RT-PCR were consistent with the IHC. The positive rates of Treg cells in lung cancer tissues, metastastic lymph nodes, corresponding normal lung tissues and bengin disease tissues were 83.9%(52/62),90.0%(18/20), 0 and 13.3%(2/15), respectively.Significant difference was also found between the former two and the latter two (P<0.01), but there was no signifcant differences between the two formers or the two latters (P >0.05). There was significant difference between the positive rate of IDO expression and the distribution of Treg cell(P<0.01). Conclusion IDO expression is up-regulated in NSCLC cell and metastastic lymph nodes. Treg cell is positive in lung cancer tissues and metastastic lymph node. These results have importment implication that the IDO(+) cancer cell might be concerned with the tumor immune tolerance by inducing the proliferation of Treg cells .